GC-olfactometric characterisation of off-odours in commercially packaged rocket leaves. (September 2020) - Raffo, Antonio; Moneta, Elisabetta; Ferrari Nicoli, Stefano; Paoletti, Flavio
Highlights: A non-destructive method was developed for off-odour characterisation of packaged rocket. Methanethiol, dimethyl sulfide and dimethyl disulfide were major off-odorants. Four unidentified solvent-smelling compounds were detected in most of the analysed products. No volatile compound released by the package was detected as odour-active. Sulfur compounds were the best candidates as indicators of off-odour formation. Abstract: A non-destructive analytical method based on HeadSpace-Solid Phase MicroExtraction/GC-Olfactometry-MS (HS-SPME/GC-O-MS) for characterisation of odour-active compounds released within packages of rocket leaves was developed. Then it was applied, along with sensory olfactory evaluation, to ten commercial products, close to the expiration date, to identify the volatiles responsible for the off-odour perception upon the opening of the bag. Twenty-nine volatiles were detected by GC-MS within the packages, whereas only eleven odour-active regions were detected by GC-O in at least three of the commercial products. Besides dimethyl sulfide and dimethyl disulfide, also methanethiol was identified as major odour-active compound associated to off-odour notes, such as rotten leaves and faecal. Acetic acid and 2, 4-dithiapentane were also tentatively identified as major off-odorants. Four structurally related volatile compounds, characterised by a solvent-like note and still unidentified, were clearly detected as odour-active but their role in off-odour perception remained to be elucidated. Among the different classes of volatiles detected in the headspace of rocket stored under modified atmosphere packaging, in the present and in previous studies, only the group of sulfur compounds consistently appeared to be related to off-odour perception and thus may be considered the best candidate as indicator of off-odour formation.